2016
DOI: 10.1039/c6tc01207h
|View full text |Cite
|
Sign up to set email alerts
|

Single-step synthesis of hyperbranched, luminescent Mn2+-doped ZnSe1−xSx nanocrystals using dichalcogenide precursors

Abstract: Taking advantage of dichalcogenide precursors, a simple, single-step heat-up method for obtaining Mn 2+ -doped ZnSe1-xSx nanocrystals (NCs) is presented. Tuning the ratios of diselendide and disulfide precursors results in alloys with varying shape, size and composition. When diphenyldiselenide (Ph2Se2) is used, highly branched networks of small NCs form. Dimethydisulfide (Me2S2) induces formation of larger NCs with less branching. Mixtures of the two exhibit branching proportional to the amount of Ph2Se2 vs M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…The samples were prepared in a cuvette with a stir bar. A syringe pump was used for the titration, with injection of thiol via a syringe as described previously [ 66 ]. While stirring, spectra were taken at intervals of 2–30 min, depending on sample brightness and sensitivity.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were prepared in a cuvette with a stir bar. A syringe pump was used for the titration, with injection of thiol via a syringe as described previously [ 66 ]. While stirring, spectra were taken at intervals of 2–30 min, depending on sample brightness and sensitivity.…”
Section: Methodsmentioning
confidence: 99%
“…Dichalcogenides have been used to synthesize nanocrystals of different ternary, quaternary, and quinary metal chalcogenide, such as ZnSe 1– x S x , Cu 2 ZnSn­(SSe) 4 , Cu 2 CdSn­(S 1– x Se x ) 4 , Sn x Ge 1– x Se, Cu 2– x SySe 1– y , Cu 2 SnSe 3 , and CuFeSe 2 . But there are just a few studies on reaction of mixtures of dichalcogenides.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembly and oriented attachments of NCs leads to formation of new structures as well. , Park et al reported formation of massive supra-QDs of CdS, CdSe, CdTe, and CdSeTe using TOP solutions of the corresponding chalcogenides . In their study, spherical NCs are made through self-assembly of small zinc blend spherical QDs .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations